Scansione laser per il rilievo dei giardini storici - Tucci, Grazia; Conti, Alessandra; Fiorini, Lidia (GEOmedia, 2013)
The 1981 ICOMOS -IFLA Florence Charter and the subsequent debates pointed out the problems of the conservation of historical gardens, including their survey. However, traditional survey techniques proved to be unsuitable to represent properly the organic forms (both natural and built) of the historical gardens and, in particular, the Mannerist artificial grott oes encrusted with rustic mosaics and sponge-like rocks. The new laser scanner surveys of main remains of the Pratolino Park show how it's possible accurately describe very complex artifacts too, as the giant Appennino statue. The new surveys show the relation between architectural and natural elements in a realistic way, helping knowledge, conservation and communication projects.